Bradyrhizobium archetypum sp. nov., Bradyrhizobium australiense sp. nov. and Bradyrhizobium murdochi sp. nov., isolated from nodules of legumes indigenous to Western Australia. Issue 8 (15th August 2020) - Helene, Luisa Caroline Ferraz; Klepa, Milena Serenato; O'Hara, Graham; Hungria, Mariangela
Abstract : The genus Bradyrhizobium is considered as the probable ancestor lineage of all rhizobia, broadly spread in a variety of ecosystems and with remarkable diversity. A polyphasic study was performed to characterize and clarify the taxonomic position of eight bradyrhizobial strains isolated from indigenous legumes to Western Australia. As expected for the genus, the 16S rRNA gene sequences were highly conserved, but the results of multilocus sequence analysis with four housekeeping genes ( dnaK, glnII, gyrB and recA ) confirmed three new distinct clades including the following strains: (1) WSM 1744 T, WSM 1736 and WSM 1737; (2) WSM 1791 T and WSM 1742; and (3) WSM 1741 T, WSM 1735 and WSM 1790. The highest ANI values of the three groups in relation to the closest type strains were 92.4, 92.3 and 93.3 %, respectively, below the threshold of species circumscription. The digital DNA–DNA hybridization analysis also confirmed new species descriptions, with less than 52 % relatedness with the closest type strains. The phylogeny of the symbiotic gene nodC clustered the eight strains into the symbiovar retamae, together with seven Bradyrhizobium type strains, sharing from 94.2–98.1 % nucleotide identity (NI), and less than 88.7 % NI with other related strains and symbiovars. Morpho-physiological, phylogenetics, genomic and symbiotic traits were determined for the new groups and our data support the description of three new species, Bradyrhizobium archetypum sp. nov., Bradyrhizobium australiense sp. nov. and Bradyrhizobium murdochi sp. nov., with WSM 1744 T (=CNPSo 4013 T =LMG 31646 T ), WSM 1791 T (=CNPSo 4014 T =LMG 31647 T ) and WSM 1741 T (=CNPSo 4020 T =LMG 31651 T ) designated as type strains, respectively.